PERENCANAAN LANSKAP KAWASAN PENERAPAN INOVASI TEKNOLOGI PETERNAKAN PRUMPUNG BERBASIS RAMAH LINGKUNGAN - Djatmiko Pinardi; Anton Gunarto; Santoso Santoso (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
The needs of animal protein especially of meats, is increasing from year to year in line with the rising numbers of people as well as an enhanced awareness of Indonesian people about fulfilling the nutrition. One of the efforts can be done to get fresh meat for consumption at their own volition was by raising the standard of the population and productivity of low class ruminants to set up their cattle on a more sustainable path. The purpose of this activity was proposed the framework for the landscape of a planning at the office of KAPITAN that serves as a means of the dissemination of technological innovations, a place to conduct field studies and mean engineering technology and shall be promulgated by the application of the concept of GFP. Material and methode to materialize this needs to be a manual the cultivation of its beef cattle (Good Farming Practices). The concept of GFP is the application of the efficiency of production with must pay attention to the environmental factors in the business of a farm. Several factors that must be considered include cattle that are reared, feed given, the management of the cost of maintenance, left the care of his facilities as well as the surrounding environment. The concept of GFP is the application of the efficiency of production with must pay attention to the environmental factors in the business of a farm. Several factors that must be taken care are its industrial activity among others cattle that are reared, feed given, the management of the cost of maintenance, the facilities of maintenance as well as the surrounding environment. Result and discussions, the application of the concept of GFP requires good managerial and qualified human resources to maintain under strict supervision and in a continuous way. The department for The Assessment and Application of Technology (BPPT) that plan to build “the area of the application of technological innovations of animal husbandry (KAPITAN) Prumpung Gunung Sindur Bogor districts” is trying to participate in the application of the concept of GFP. Conclusion, Kapitan Prumpung is expected to beneficial in helping on the development of food security in the delivery of animal protein origin of ruminants through innovation in the field of animal husbandry and the increase in human resources of animal husbandry Keywords: Husbandry Landscape, Good Farming Practices, Environmental Friendly